Mental Symptoms and Stress of Hospitalized Schizophrenia Patients With 2019 Novel Coronavirus Disease: An Observation Study - Ma, Jun; Jiang, Tao; Huang, Hanjun; Li, Ruihua; Zhang, Lin; Liu, Lianzhong; Liu, Xuebing (Frontiers in Psychiatry, 2021)
Background: The 2019 novel coronavirus disease (COVID-19) is an acute respiratory infectious disease caused by the new coronavirus (SARS-CoV-2). Many schizophrenic patients were infected with COVID-19 in Wuhan City, Hubei Province, where the epidemic was first reported and the most serious in China. In this study, hospitalized schizophrenia patients with COVID-19 were recruited as research subjects to explore the changes in psychiatric symptoms and stress. Methods: To sort and isolate potential COVID-19-infected patients, an isolated ward was set up from January 30, 2020, to March 30, 2020. Schizophrenia patients with COVID-19 were referred to this ward, and long-term hospitalized cases were included in this study. The Positive and Negative Syndrome Scale and Perceived Stress Scale were used to evaluate the severity of mental symptoms and psychological stress in the early stage of the outbreak of COVID-19, after the diagnosis of COVID-19 and after recovery. At the time of diagnosis, we also extracted the patient's routine blood, biochemical and other indicators and asked the patient's perception of COVID-19. Results: During the observation period, twenty-one hospitalized schizophrenia patients with COVID-19 were recruited in this study. The changes in PANSS scores were not significant (p = 0.23 baseline vs. diagnosed, p = 0.40 cured vs. diagnosed). The CPSS scores increased significantly after diagnosis and transfer to the isolation ward (p = 0.00 baseline vs. diagnosed, p = 0.00 cured vs. diagnosed). The course of schizophrenia was a protective factor of stress levels to cases (t = -3.25, p = 0.01), and patients' perception of COVID-19 was a risk factor (t = 2.48, p = 0.04). The final multiple linear regression model was statistically significant (F = 8.16, p = 0.00). Conclusion: Hospitalized schizophrenia patients with COVID-19 had increased stress levels but relatively stable mental symptoms after isolated treatment.